Browning of adipose tissue and increased thermogenesis induced by Methotrexate. Issue 11 (7th October 2021) - Verma, Narendra; Perie, Luce; Corciulo, Carmen; Leucht, Philipp; Ramkhelawon, Bhama; Cronstein, Bruce N.; Mueller, Elisabetta
Abstract: Methotrexate (MTX) is widely used for the treatment of rheumatoid arthritis due to its well‐known anti‐inflammatory role in immune cells but its impact on brown and beige adipose tissue biology has not yet been investigated. Here, we present the novel evidence that MTX treatment increases the gene expression of thermogenic genes in brown and beige adipose tissues in a fat cell autonomous manner. Furthermore, we show that treatment of mice with MTX is associated with cold resistance, improved glucose homeostasis, decreased inflammation, and reduced hepatosteatosis in high‐fat diet states. Overall, our data provide novel evidence of a role of MTX on thermogenic tissues not previously appreciated.